Using bivalves in an alternative testing method of freshwater pollution with heavy metals - Sárkány-Kiss Endre; Braun Mihály (2002)
In order to test an alternative method on freshwater pollution with heavy metals, individuals of Unio crassus were exposed in cagcs in polluted reaches of the Some? River. Their time-related bioaccumulation was registered and compared with control samples.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok